Geochronology of Neoproterozoic syn-rift magmatism in the Yangtze Craton, South China and correlations with other continents: evidence for a mantle superplume that broke up Rodinia - Li, Zheng-Xiang; Kinny, Peter; Zhou, H. (Elsevier Science BV, 2003)
Neoproterozoic granitic intrusions in South China have traditionally been interpreted as related to orogenesis, marking thecratonisation of the Yangtze Block. However, a number of ca. 830-820 Ma granitoids and mafic-ultramafic intrusions unconformablyoverlain by Neoproterozoic rift successions have recently been reinterpreted as being related to a mantle plume duringthe breakup of the supercontinent Rodinia. In this paper, we report SHRIMP zircon U-Pb ages from granitoids and gabbros thatare closely related to the Neoproterozoic rifting event, and one age from a volcanic unit in the rift successions. We demonstrate that there were two major phases of widespread bimodal magmatism in South China during the Neoproterozoic. The first one,at ca. 830-795 Ma, started before the continental rift but continued into the first two stages of the rifting. The second one, ca.780-745 Ma, occurred during the later stages of the rifting. Some co-magmatic mafic dykes have rare-earth element and traceelement distribution characteristic of continental flood basalts. Similar age patterns of Neoproterozoic anorogenic magmatismare recorded in most other Rodinian continental blocks, such as Australia, India, Madagascar, Seychelles, southern Africa andLaurentia. The widespread occurrence and protracted duration (ca. 85 million years) of such anorogenic magmatism require alarge and sustained heat source. We interpret these magmatism as results of a mantle superplume beneath Rodinia, which wasresponsible for the breakup of the supercontinent during the Neoproterozoic.